Regulation of muscle protein synthesis in an in vitro cell model using ex vivo human serum. Issue 6 (5th May 2018) - Carson, Brian P.; Patel, Bijal; Amigo‐Benavent, Miryam; Pauk, Martina; Kumar Gujulla, Sunil; Murphy, Sylvia M.; Kiely, Patrick A.; Jakeman, Philip M.
Abstract : New Findings: What is the central question of this study? Can medium conditioned by ex vivo human serum regulate muscle protein synthesis in skeletal muscle cells in vitro ? What is the main finding and its importance? This study demonstrates that medium conditioned by ex vivo human serum can regulate muscle protein synthesis in skeletal muscle cells in vitro via the mammalian Target of Rapomycin (mTOR) pathway, and this can be regulated differentially by fed and fasted ex vivo human serum. Abstract: Human serum embodies the integrated systemic response to any condition or perturbation, which may regulate muscle protein synthesis (MPS). Conditioning of medium with human serum represents a physiologically relevant method of regulating MPS in vitro . The primary purpose of the study was the development of a model using ex vivo human serum to condition medium and regulate MPS in in vitro skeletal muscle cells. Four young healthy men reported to the laboratory after an overnight fast and were fed with 0.33 g (kg body mass) −1 whey protein. Blood samples were taken before (Fasted) and 60 min postprandial (Fed). Fully differentiated C2C12 skeletal muscle cells were nutrient and serum deprived for 1 h and subsequently treated with medium conditioned with Fasted or Fed ex vivo human serum (20%) for 4 h. The MPS was measured using the surface sensing of translation technique and activation of mTOR, P70S6K and 4EBP1 by Western blot. Fasted and fed ex vivo human serum increased MPS ( P < 0.05). Although a strong effect (ƞ 2 = 0.36) for increased MPS in Fed relative to Fasted was observed, this was not statistically significant ( P > 0.05). Activation of mTOR, P70S6K and 4EBP1 was significantly increased after treatment with Fed compared with Fasted ex vivo human serum ( P < 0.05). Here, we developed and optimized the conditions for culture of C2C12 skeletal muscle cells, measurement of MPS and signalling in medium conditioned by ex vivo human serum. Furthermore, the functionality of the model was demonstrated by comparison of the response to medium conditioned by Fasted and Fed ex vivo human serum. Abstract :